Alveolar Macrophage Immunometabolism and Lung Function Impairment in Smoking and Chronic Obstructive Pulmonary Disease - Cloonan, Suzanne (My University, 2020)
Metabolic plasticity involving shifts between mitochondrial respiration and glycolysis is emerging as a crucial component of innate immune cell function. The number of alveolar macrophages (AMs), the most abundant antigen-presenting cells in the lung, is increased in the lungs of individuals with chronic obstructive pulmonary disease (COPD), associating with disease severity and areas of lung destruction (1, 2). However, COPD AMs exhibit dysfunctional responses to infection and have lower phagocytic and bactericidal activity (3–5). Metabolism is a key determinant of immune cell function and is a vital component governing macrophage adaptation and responses. Metabolic reprogramming involving a shift from ATP production via the mitochondrial electron transport chain, toward anaerobic respiration via glycolysis, is an important proinflammatory effector function of macrophages (6). The presence and nature of any functional shifts in AM metabolic activity in COPD has not been determined.
PUBLISHED